Targeted exome sequencing for molecular diagnosis of pediatric Alport syndrome in Southwest China - Zhou, Cong; Xiao, Yuanyuan; Wei, Xing; Wang, Jing; Liu, Shanling (Frontiers in Genetics, 2025)
BackgroundAlport syndrome (AS) is an inherited disorder affecting basement membrane collagen IV. AS is characterized by hematuria and progressive renal failure, accompanied by high-frequency sensorineural deafness and ocular changes. AS is caused by collagen type IV α3 chain (COL4A3), α4 chain (COL4A4), and α5 chain (COL4A5) variants. We aimed to identify the genetic variants in a cohort of 20 children with clinically suspected AS in Southwest China.ResultsWe detected 21 COL4A3, COL4A4, and COL4A5 variants in 20 probands. Of these variants, 16 (16/21, 76.2%) were classified as pathogenic/likely pathogenic and 5 (5/21, 23.8%) of uncertain significance according to the American College of Medical Genetics and Genomics criteria. A total of 11 (11/21, 52.4%) and 10 (10/21, 47.6%) variants were known and novel, respectively.ConclusionWe performed molecular diagnosis on 15 patients using targeted exome sequencing. Our findings indicate additional COL4A3, COL4A4, and COL4A5 variants as involved in AS, having implications for genetic diagnosis, therapy, and counseling of affected families.